PENGUATAN BADAN USAHA MILIK KAMPUNG (BUMKAM) DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI KABUPATEN SIAK PROVINSI RIAU - Dahlan Tampubolon (Universitas Negeri Medan, 2021)
Integrated community service with the 2020 UNRI Real Work Lecture (Kukerta) aims to increase the knowledge of the government and village communities about the role of Village-Owned Enterprises (BUMKam). It also aims to prepare BUMKam managers to be more optimal in developing BUMKam through management training and making business road maps. The object of its activities is BUMKam Dayun Mandiri. Training and mentoring are the main methods of this service activity. Starting with a survey to identify needs and possible solutions. Community service activities were started by making an alignment by the team and apparatus and the community at the Kukerta post. The FEB UNRI service team together with the apparatus and the community prepared a plan. Kukerta participants are trained to be facilitators by accompanying lecturers at the Kukerta locations. Then training for the preparation of BUMKam business strategic planning. Implementation of monitoring and evaluation to see progress, supervise processes and activities continuously, identify problems and deviations that often arise, formulate problem solving and compile periodic progress reports over a specified time period. BUMKam managers accompanied by Kukerta participants have been able to improve the BUMKam administration process. Both administrative management, financial accountability reports and loan distribution to micro and small businesses.